2022
DOI: 10.29244/jmf.v13i2.41239
|View full text |Cite
|
Sign up to set email alerts
|

Pemetaan Spasial Dan Temporal Status Pemanfaatan Ikan Kerapu Di Perairan Teluk Saleh, Nusa Tenggara Barat

Abstract: The Saleh Bay is one of the bays in West Nusa Tenggara utilized as the grouper fishing ground. However, in the previous spawning potential ratio study, some grouper species have been overexploited in Saleh Bay. This study aimed to estimate the status of grouper utilization with a catch per unit effort (CPUE) approach and the spatio-temporal fishing intensity of grouper in fishing grounds in Saleh Bay. Data were gathered using the fish landing data and geo-reference of fishing ground grouper in Saleh Bay. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…), and mackerel scad (Decapterus spp. ), and artificial lures [61]. In addition to using fresh bait, troll lines in Saleh Bay also employ artificial lures (made of plastic that resembles a fish), which accounts for a very high proportion of epinephelid catches.…”
Section: Variation Of Catches Among Fishing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…), and mackerel scad (Decapterus spp. ), and artificial lures [61]. In addition to using fresh bait, troll lines in Saleh Bay also employ artificial lures (made of plastic that resembles a fish), which accounts for a very high proportion of epinephelid catches.…”
Section: Variation Of Catches Among Fishing Methodsmentioning
confidence: 99%
“…Further analysis of the five main fishing methods (bottom longline, speargun, handline, drop line, and troll line) revealed that bottom longlines yielded the highest CPUE. This is likely due to the nature of bottom longlines, which can deploy 100-250 hooks in a single setting [61]. This number is much greater than the single line and hook used in handlines or troll lines.…”
Section: Variation Of Catches Among Fishing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jika dibandingkan dengan penelitian ini, ukuran maksimal kedua jenis ikan tersebut tidak berbeda jauh. Dengan pemahaman ini, terungkap bahwa ikan kerapu yang memiliki karakteristik ukuran dan bobot maksimal dapat menjadi landasan penting dalam pengelolaan dan pelestarian sumber daya ikan kerapu (Darmawan et al, 2022). Dengan memahami keberadaan serta ukuran tubuh ini, praktisi perikanan dan pengelola sumber daya laut dapat mengambil langkah-langkah yang lebih terarah dalam menjaga keseimbangan populasi ikan kerapu di berbagai habitat dan perairan (Blount et al, 2021;Niz et al, 2023;Hehanussa, 2024 ).…”
Section: Deskripsi Jenis Dan Ukuan Ikan Kerapu Pasar Arumbaiunclassified
“…Secara ekologis, penangkapan ikan di bawah Lm berpengaruh terhadap keseimbangan rantai makanan di perairan (Syadli et al 2022). Darmawan et al (2022) berpendapat kepatuhan terhadap peraturan pemerintah mengenai ukuran ikan dapat mempertahankan kelestarian sumberdaya ikan. Kurangnya pemahaman keberlanjutan sumberdaya ikan harus menjadi perhatian pengelolaan perikanan.…”
Section: Penilaian Indikator Eafmunclassified